2017
DOI: 10.1530/erp-17-0005
|View full text |Cite
|
Sign up to set email alerts
|

Speckle tracking echocardiography in acute lupus myocarditis: comparison to conventional echocardiography

Abstract: AimsLupus myocarditis occurs in 5–10% of patients with systemic lupus erythematosus (SLE). No single feature is diagnostic of lupus myocarditis. Speckle tracking echocardiography (STE) can detect subclinical left ventricular dysfunction in SLE patients, with limited research on its utility in clinical lupus myocarditis. We report on STE in comparison to conventional echocardiography in patients with clinical lupus myocarditis.Methods and resultsA retrospective study was done at a tertiary referral hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
2
18
0
1
Order By: Relevance
“…In fact, GLS impairment has an early diagnostic and prognostic value. 16 This finding is in line with the results of a study by Huang et al, 27 who reported a reduction in the LV GLS in 2D echocardiography in their patients with lupus by comparison with their healthy subjects. A similar study, conducted in 2016 with the aid of speckle-tracking echocardiography to evaluate strain indices in patients suffering from lupus, indicated that the strain indices were decreased in the treatment-resistant lupus group compared with the non-resistant lupus group.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, GLS impairment has an early diagnostic and prognostic value. 16 This finding is in line with the results of a study by Huang et al, 27 who reported a reduction in the LV GLS in 2D echocardiography in their patients with lupus by comparison with their healthy subjects. A similar study, conducted in 2016 with the aid of speckle-tracking echocardiography to evaluate strain indices in patients suffering from lupus, indicated that the strain indices were decreased in the treatment-resistant lupus group compared with the non-resistant lupus group.…”
Section: Discussionsupporting
confidence: 90%
“…1-10 Lupus myocarditis is a serious manifestation of SLE which occurs in 5% to 10% of patients with SLE. 11-16…”
Section: Introductionmentioning
confidence: 99%
“…The second most common cause of LV diastolic dysfunction in SLE patients is probably arterial hypertension, which is a highly prevalent condition (25% to 35%) in these patients [34,35]. Premature peripheral arterial stiffness independent of arterial hypertension causing increased LV afterload and LV mass may be another pathogenetic factor [36]. Finally, primary myocarditis is a rare cause of LV diastolic dysfunction in these patients.…”
Section: Major Findingsmentioning
confidence: 99%
“…14 In SLE patients with clinical lupus myocarditis, reduced strain is also prognostic of persistent systolic dysfunction following treatment. 20 There are two pediatric studies suggesting that impaired LV systolic strain is present in children with pSLE. 21,22 However, the majority of these patients were still using glucocorticoids, which can influence afterload.…”
Section: Introductionmentioning
confidence: 99%
“…20) of pSLE subjects had a history of lupus nephritis, one subject had a history of serositis, and one had a history of neuropsychiatric SLE. Average disease activity at the initial onset of SLE was high (mean baseline SLEDAI of 12.4 [SD 7.3]).…”
mentioning
confidence: 99%